2005
DOI: 10.1186/1465-9921-6-88
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of losartan for pulmonary hypertension in chronic obstructive pulmonary disease

Abstract: Background: Morbidity in COPD results from a combination of factors including hypoxia-induced pulmonary hypertension, in part due to pulmonary vascular remodelling. Animal studies suggest a role of angiotensin II and acute studies in man concur. Whether chronic angiotensin-II blockade is beneficial is unknown. We studied the effects of an angiotensin-II antagonist losartan, on haemodynamic variables, exercise capacity and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 36 publications
(31 reference statements)
1
30
0
7
Order By: Relevance
“…Treatment with conventional vasodilators such as CCBs is not recommended because they may impair gas exchange due to the inhibition of hypoxic pulmonary vasoconstriction [406][407][408] and because of their lack of efficacy after long-term use [409,410].…”
Section: Therapymentioning
confidence: 99%
“…Treatment with conventional vasodilators such as CCBs is not recommended because they may impair gas exchange due to the inhibition of hypoxic pulmonary vasoconstriction [406][407][408] and because of their lack of efficacy after long-term use [409,410].…”
Section: Therapymentioning
confidence: 99%
“…ACE activity was increased and correlated with the degree of RV hypertrophy in the chronically hypoxic rat (6). The results of these studies led to the first double-blind placebo-controlled trial of losartan in patients with pulmonary hypertension associated with chronic obstructive pulmonary disease (7). Although this trial was underpowered, a post hoc analysis suggested benefit in patients with more severely elevated pulmonary hemodynamics.…”
Section: To the Editormentioning
confidence: 99%
“…In contrast, in a separate study 48 weeks of losartan led to little beneficial result in 40 COPD patients with PH. 59 Similarly, a single administration of nifedipine resulted in modest improvement in mean PAP without much change in PVR in 33 COPD patients. 60 Importantly, in a series of 6 patients with PH secondary to COPD, nifedipine reduced PVR but decreased arterial PaO 2 as a result of alteration in V/Q matching.…”
Section: Vasodilatorsmentioning
confidence: 99%